Hacienda puertas a glimpse at a Filipino-Spanish sugarcane plantation in Isabela, Negros Occidental, 1900-2006. - Sano, Ralph Vincent Puertas
The study aims to know the origin of Hacienda Puertas; to present the growth and development of the hacienda; to identify the personalities that managed the hacienda; to understand the management, operations, and policies of the hacienda; and to show the significance of the hacienda to the Puertas family, to the laborers, and to the town of Isabela, Negros Occidental., The data were gathered from a journal written by the past and present owners of the hacienda which is now the property of the present owner. Interviews on key informants like the present owner, the laborers, the milling operator, and a town official were done by the researcher to gain knowledge about the hacienda. The researcher found out that the origin of the hacienda was in 1900 when Nicolas E. Puertas founded Hacienda Puertas after the land was given to him by his father. The hacienda encountered many problems and difficulties and had many developments. There were six owners from the start of the hacienda up to the present. There were many things implemented in the management, operations, and policies of the hacienda that led to its growth and development. The hacienda was significant to the family of the owner, to the laborers, and to the town in some aspects. Basically Hacienda Puertas was one of the haciendas that surrounded the town of Isabela, Negros Occidental and it contributed to the development and improvement of the town. The taxes paid by the hacienda were used by the government to build public constructions like roads and bridges. The income of the town became higher and the businesses in it flourished due to the success of the haciendas in producing sugar.